(x-2)/(x+3)=(x-1)/(x+6) Solve for x
Please note that if I apply the least common multiple of both denominators of your expression is:
(x+3) (x+6), so
we can accept all values of x such that x is not equal to -3, and x is not equal to -6.
Next, we can write:
(x-2) (x+1) = (x-1) (x+3)
and applying the distributive property of multiplication over addition at both sides of the last above expression, we get:
x^2 + 4x - 12 = x^2 + 2x - 3
after a simplification, I can write:
4x - 12 = 2x - 3
2x = 9
dividing both sides by 2, I get your answer as below:
x = 9/2
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?